M&B3 - Croushore, Dean. (Stamford, Connecticut : Cengage Learning Asia Pte Ltd, 2015)
Created by the continuous feedback of a "student-tested, faculty-approved" process, M&B delivers a visually appealing, succinct print component, tear-out review cards for students and instructors and a consistent online offering with CourseMate that includes an eBook in addition to a set of interactive digital tools all at a value-based price and proven to increase retention and outcomes. M&B, 3E's brief, focused approach reads more like a business periodical than a text.
Part One. Money and the financial system -- Part Two. Fundamentals of banking -- Part Three. Macroeconomics -- Part Four. Monetary policy.
Includes index.
Keywords: BANKS AND BANKING